Tafsir Ayat Al-Qur’an Sebagai Pedoman Hidup Sekaligus Dasar Penyelenggaraan Pendidikan (QS. Al-An’am/6: 91-92, QS. Ali Imron/3: 7, 164, QS. Al-Isra’/17: 9, 82) - Sulkifli; Fikriyanti Putri Pratama; Dewi Arsinta; Muh. Anwar Abdullah (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
study aims to analyze the role of Qur’anic verses as a guide for life as well as a foundation for the implementation of Islamic education, focusing on QS. Al-An’am (6): 91–92, QS. Ali Imran (3): 7 and 164, and QS. Al-Isra’ (17): 9 and 82. This research employs a qualitative method using a thematic exegesis approach (tafsīr mawḍū‘ī), through a literature review of both classical and contemporary tafsir sources. The findings reveal that the Qur’an holds a central role as hudan (guidance), nur (light), and shifa’ (healing), which directs human beings toward a balanced life in spiritual, moral, and intellectual dimensions. QS. Al-An’am highlights the Qur’an as a source of guidance and blessing, QS. Ali Imran explains the foundational principles of education through the understanding of muhkam and mutashabih verses and emphasizes the role of the Prophet as an educator, while QS. Al-Isra’ underlines the Qur’an’s function as a guide to the straight path and a source of spiritual healing. These findings indicate that the Qur’an is not merely a normative religious text, but also serves as a philosophical and practical foundation for Islamic education, aimed at developing individuals who are faithful, knowledgeable, and morally upright. Therefore, integrating Qur’anic values into educational practices is essential in addressing the challenges of modern life.